Factors associated with age at first screening for cervical cancer among adult Cape Verdean women: a cross-sectional study - Joshua Okyere; Castro Ayebeng; Kwamena Sekyi Dickson (BMC, 2024)
Abstract Background Cervical cancer ranks third in terms of cancer incidence and mortality in Cape Verde. Understanding the factors associated with the age of cervical cancer screening (CCS) is essential because it helps identify populations at risk of delayed screening, enabling targeted interventions to ensure timely detection and treatment, ultimately reducing the burden of cervical cancer. We examined the factors associated with age at first screening for cervical cancer among adult Cape Verdean women. Methods Data from the 2020 WHO STEPs survey were used. We analyzed data from 1,082 women aged 30-69 years who had ever screened for cervical cancer. Bivariable and multivariable logistic regression models were computed in STATA version 18. Results Overall, 30.6% of women in the study had their first CCS before or at age 30. Except for visits to the health facility within the last 12 months, all variables significantly predicted women's first age for CCS in the crude model. In the adjusted model, women with tertiary education showed greater odds [AORs = 9.85; 95% CI: 4.12-23.54] compared to those with no formal education. Compared to those who were never married, previously married women had significantly lower odds of screening at an early age [AOR = 0.63; 95% CI: 0.39-0.99]. Women without hypertension had higher odds [AOR = 1.66; 95% CI: 1.18-2.34] of early screening compared to those with hypertension. Also, women who were currently working had significantly higher odds of early screening than those unemployed [AOR = 1.49; 95% CI: 1.09-2.04]. Conclusion In conclusion, implementing targeted educational campaigns, addressing socio-economic barriers, and integrating cervical cancer screening into routine healthcare services can increase the early screening uptake among Cape Verdean women. There is a need to integrate CCS in the routine healthcare services of women living with hypertension. Also, the positive association between formal education and age at first screening, it is imperative for the Cape Verdean public health departments to implement comprehensive education programs within schools to promote awareness about CCS.